IMPLEMENTASI ARSITEKTUR MEVN STACK PADA SISTEM MANAJEMEN ARSIP DIGITAL FOOTAGE FILM - Adhimas Dwi Wahyu Sejati (Universitas Lampung, 2026)
Digital Agency Mengudara Komunikasi faces challenges in managing digital assets in the form of film footage, which continue to grow alongside increasing production. The current archiving process still relies on physical storage media, making it vulnerable to damage and limiting effective team collaboration. This study aims to develop a web-based digital archive management system to improve data security and accessibility. The research employs the Waterfall method and implements MEVN Stack technologies (MySQL, Express.js, Vue.js, Node.js), integrated with the Google Drive API as a cloud-based storage solution. The results show that the developed system is capable of automating the storage and management of digital archives, enabling efficient data retrieval based on categories such as Trailers, Teasers, and Posters, and improving real-time accessibility for team members. Therefore, the system effectively reduces the risk of data loss due to physical storage damage and enhances operational efficiency in managing digital archives.